An approach to stability analysis of spatial xenon oscillations in WWER-1000 reactors. (May 2015) - Parhizkari, H.; Aghaie, M.; Zolfaghari, A.; Minuchehr, A.
Highlights: The multipoint methodology is developed for xenon oscillation in the BNPP. The axial, radial and azimuthal offsets are calculated in the BOC and EOC. It is shown that the all of oscillation modes are safe in the BOC. The axial oscillation is not safe in the EOC and needs governor control system. The multipoint kinetics show good agreement for spatial oscillations. Abstract: Spatial power oscillations due to spatial distribution of xenon transient are well known as xenon oscillation in large reactors. Xenon-induced spatial power oscillations occur as a result of rapid perturbations to power distribution that cause the xenon and iodine distribution to be out of phase with the perturbed power distribution. This results in a shift in xenon and iodine distributions that causes the power distribution to change in an opposite direction from the initial perturbation. In this paper xenon-induced power oscillation is described by a system of differential equations with non-linearity between xenon and flux distributions; the dynamics of process is described by a discrete distributed parameter model, with the neutron flux, the delayed neutrons, the core temperature and the xenon and iodine concentrations as the "states" of the system. It is shown that it is possible to describe the discrete distributed-parameter as a set of coupled point-reactor models. It is also shown that using this scheme it is possible to analyze the control aspects of a multi-section large core reactor by treating only two adjacent sections of the core. To illustrate the capability and efficiency of the proposed scheme Bushehr Nuclear Power Plant, BNPP, which is a WWER-1000 reactor, is chosen to show the performance of the methodology. The axial, azimuthal and radial power oscillation at the beginning of cycle, BOC, and the end of cycle, EOC, for BNPP are investigated; the results are in good agreement with safety analysis report of the reference plant.